MEASURING HYSTERESIS LOOPS OF FERROELECTRIC POLYMERS USING THE CONSTANT CHARGING CURRENT CORONA TRIODE - Alves, Neri [UNESP]; Giacometti, J. A.; Oliveira, O. N. (American Institute of Physics (AIP), 1991)
A novel method is proposed for measuring the hysteresis loops of ferroelectric polymers. The samples need to have only one electrode and are poled by corona discharge in a constant current corona triode. It is shown how the sample surface potential and the charging current are related to the remanent polarization and coercive field, so that the hysteresis loops can be obtained. An illustrative example is given for samples of beta-PVDF for which the hysteresis cycles were remarkably close to those obtained with the traditional Sawyer-Tower circuit. Values of 80 MV/m and 70 mC/m2 were estimated for the coercive field and remanent polarization, respectively.